PROVIDE GRID ACHIEVABLE RESULTS ALLOWABLE CONTENT OF POLLUTANTS IN WASTE WATER (Municipal economy of cities (Technical science), 2013)
Rationing of pollutants in waste water entering the waterways is considered as an optimization problem. The problem of providing technologically achievable result of the calculation. We formulate an optimization problem for a single control point.